2021
DOI: 10.1186/s12889-021-12264-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with an interruption in treatment of people living with HIV in USAID-supported states in Nigeria: a retrospective study from 2000–2020

Abstract: Background Patient interruption of antiretroviral therapy (ART) continues to limit HIV programs’ progress toward epidemic control. Multiple factors have been associated with client interruption in treatment (IIT)— including age, gender, CD4 count, and education level. In this paper, we explore the factors associated with IIT in people living with HIV (PLHIV) in United States Agency for International Development (USAID)-supported facilities under the U.S. President’s Emergency Plan for AIDS Reli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 16 publications
2
11
1
Order By: Relevance
“…Our study found that adults in second-line ART regimens had a higher risk of LTFU than those in the first-line. Our finding is similar to the studies conducted in Nigeria [ 19 , 20 ] and Uganda [ 24 ], which reported a high risk of LTFU in treatment among patients on a second-line regimen. However, the finding is inconsistent with studies [ 31 , 36 ] that found patients on 1st line regimens to have an increased risk of LTFU.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found that adults in second-line ART regimens had a higher risk of LTFU than those in the first-line. Our finding is similar to the studies conducted in Nigeria [ 19 , 20 ] and Uganda [ 24 ], which reported a high risk of LTFU in treatment among patients on a second-line regimen. However, the finding is inconsistent with studies [ 31 , 36 ] that found patients on 1st line regimens to have an increased risk of LTFU.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of LTFU in adults PLHIV in the current study was similar to the findings of studies conducted in Nigeria and Gabon, where the cumulative rate of LTFU at 13-and 10-years review in Nigeria was 30.6% and 32% [19,20], while in Gabon in a 2 years review was 34.1% [21]. The study findings are in contrast to the 13.45% LTFU in a retrospective study in Northwest Ethiopia [22], 3% LTFU in a study in France [23], 12.75% LTFU in a retrospective study in Kampala-Uganda [24], 12.8% LTFU in a cohort study in South Africa [25], while a study done in Guinea and Kenya reported a prevalence of 57.61% and 54% LTFU from a 7 years follow-up study [26,27].…”
Section: Discussionsupporting
confidence: 88%
“…The Hakizayezu et al study identified other predictors, including a prior history of treatment interruption (which we could not explore as were looking at first interruption) and good perception toward the whole-of-life treatment[13]. Aliyu et al identified additional predictors including HIV viral load indication and result as well as age[17] (which was not predictive in this study or in the Tomescu et al study[16]), and regimen at the start of ART. Other identified predictors in the Tomescu et al study included geo-political zone, regimen line, and viral load suppression[16].…”
Section: Discussionmentioning
confidence: 82%
“…Logistic regression captured some predictors of IIT, including female sex. In the 2019 study by Aliyu et al[17] 2021 study by Tomescu et al[16], the 2022 study by Hakizayezu et al[13], and a 2020 study by Abebe et al[20] sex was found to be predictive of interruptions in care; however, in all of these studies, the men were at a higher risk of interruption or its proxy such as loss to follow up. Our findings may differ from those of prior studies because we were restricted to those who interrupted but re-engaged in care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation